2012
DOI: 10.4103/0971-3026.95407
|View full text |Cite
|
Sign up to set email alerts
|

Utility of gray-scale ultrasound to differentiate benign from malignant thyroid nodules

Abstract: Objective:The objective was to assess the utility of gray-scale USG to identify patterns of thyroid nodules and to correlate the characteristics of benign and malignant nodules with pathological diagnosis.Materials and Methods:From September 2009 to August 2010, a total of 203 patients (17 males and 186 females), with 240 nodules detected at USG, were included in this study. The characteristics of each nodule were determined. The results were then compared with fine needle aspiration (FNA)/histopathological di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 13 publications
2
21
0
1
Order By: Relevance
“…Sensitivity of US in detecting thyroid malignancy in the present study was 83.3% which was similar to a study of 203 patients from September 2009 to August 2010 where the overall sensitivity of thyroid US for diagnosing a malignant nodule was 81.8%. 22 Among cervical lymphadenopathy, out of 8 malignant lymph nodes, US correctly diagnosed 7. Out of these, 7 were metastatic lymph nodes and 1 was Hodgkin's lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity of US in detecting thyroid malignancy in the present study was 83.3% which was similar to a study of 203 patients from September 2009 to August 2010 where the overall sensitivity of thyroid US for diagnosing a malignant nodule was 81.8%. 22 Among cervical lymphadenopathy, out of 8 malignant lymph nodes, US correctly diagnosed 7. Out of these, 7 were metastatic lymph nodes and 1 was Hodgkin's lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings (sensitivity and specificity of 65.9% and 87.2% respectively) were reported in another study. 1 We also found that hypoechogenicity had a high negative predictive value of 98.8% indicating that nodules which were not hypoechoic are likely to be malignant in only 4.2% of cases. We observed that US feature of microcalcification had a high specificity (96.5 %) and less sensitivity (16.6%).…”
Section: Resultsmentioning
confidence: 78%
“…Many sonological features like irregular margins, micro calcifications, taller than wider shape, marked hypoechogenicity have been shown to have predilection for malignancy. [1][2][3][4][5][6][7] However, there is also overlap in the appearance of benign and malignant t hyroid nodules. Due to inconsistent predictive value of USG features, fine needle aspiration and cytopathological…”
Section: Introductionmentioning
confidence: 99%
“…Tiroid nodüllerinin tespitinde fizik muayene önemlidir ve yapılan klinik çalışmalarda, dikkatli bir muayene ile toplumun %3-7 sinde nodül tespit edilebileceği gösterilmiştir (8). Türkiye'de yapılan çalışmalarda, bu oran yaklaşık %2,8 olarak bulunmuştur (9).…”
Section: Discussionunclassified